Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3171/2015.4.jns15120
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgery for schizophrenia: an update on pathophysiology and a novel therapeutic target

Abstract: Schizophrenia is a heterogeneous disorder characterized by varying degrees of positive psychotic symptoms, negative symptoms, and cognitive impairment. 48 With a prevalence of 1.1% in the US, 93 schizophrenia is a major health burden, increasing the risk for numerous adverse outcomes, including the inability to maintain a stable residence, maintain a job, or find a spouse. 39Moreover, 10%-30% of patients with schizophrenia have little or no response to antipsychotic treatment. 68 Limited treatment options are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 126 publications
0
22
0
Order By: Relevance
“…It is thus suggested that the striatum can be a therapeutic target for promoting SVZ neurogenesis. Clinically, this is achievable using deep brain stimulation (DBS) and brain-implanted devices of closed-loop technology (Krook-Magnuson et al, 2015; Mikell et al, 2016; Velasques et al, 2014). Other novel methods including optogenetics and pharmacogenetic may also have clinical potential of specific stimulation (Little and Brown, 2014; Peled, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus suggested that the striatum can be a therapeutic target for promoting SVZ neurogenesis. Clinically, this is achievable using deep brain stimulation (DBS) and brain-implanted devices of closed-loop technology (Krook-Magnuson et al, 2015; Mikell et al, 2016; Velasques et al, 2014). Other novel methods including optogenetics and pharmacogenetic may also have clinical potential of specific stimulation (Little and Brown, 2014; Peled, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, we hypothesize that in this clearly defined subgroup, the pathophysiology involves deep brain structures that are not in reach of rTMS or trans­cranial direct current stimulation. In theory, deep brain stimulation would be the proper method for reaching these deep-seated targets [135], and our studies indicate the specific patient population for this method. However, we have little hope that this could ever become standard treatment for this patient group, which, by definition, is pathologically suspicious and often lacks a feeling of illness and confidence in any medical treatment.…”
Section: Clinical Implications Of Synopsismentioning
confidence: 99%
“…In this system, the ventral tegmental area (VTA) makes connections with the nucleus accumbens (NAcc), the septal nuclei, and the amygdala via the medial prosencephalic bundle, and with the prefrontal cortex (PFC) via the cingulate gyrus. [1][2][3]10,11 It is proposed that in psychosis the deregulation of the release of dopamine initially results in an incorrect reward stimulus that would be ignored in another situation, leading to an aberrant overhang in the upper cortical levels, and this would translate clinically as positive symptoms. 11 Activation of the hippocampus leads to the release of dopamine in the mesolimbic pathway.…”
Section: Circuitrymentioning
confidence: 99%
“…[1][2][3]10,11 It is proposed that in psychosis the deregulation of the release of dopamine initially results in an incorrect reward stimulus that would be ignored in another situation, leading to an aberrant overhang in the upper cortical levels, and this would translate clinically as positive symptoms. 11 Activation of the hippocampus leads to the release of dopamine in the mesolimbic pathway. Studies have shown that its hyperactivation would be the cause of the hyperdopaminergic state, since its activation stimulates GABAergic neurons in the NAcc, which, in turn, inhibits the GABAergic neurons of the globus pallidus (GP), which are responsible for the inhibition of the dopaminergic neurons in the VTA.…”
Section: Circuitrymentioning
confidence: 99%
See 1 more Smart Citation